A conceptual emotion-based model to improve students engagement in a classroom using agent-based social simulation - Subramainan L.; Mahmoud M.A.; Ahmad M.S.; Yusoff M.Z.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Education; Teaching; Agent based social simulation; Data collection; Emotional engagements; Emotional state; emotions; Engagement levels; Student engagement; Work in progress; Students